Evaluation of an in-service training institute for elementary science teachers - Dimaguila, Linda Aguilar (Saturnino) 1926- (s.n.], 1970)
An evaluative study of an In-Service Training Institute for Elementary Science Teachers was conducted for the purpose of discovering its objectives in terms of the effect of the training on the participants and to seek information that may help in making the program more effective. The study tried to assess the impact of the Science Education Center Curriculum materials on the teachers and the teaching-learning process. The results of the study serve as a diagnostic tool that will enable the Zamboanga State College to determine the areas for improvement of the training institutes.